Women in Southeast Asian Nationalist Movements : A Biographical Approach - Ting, Helen, 1964-; Blackburn, Susan, 1947- (Book collections on Project MUSE., 2013)
In many Southeast Asian countries, anti-colonial nationalist struggles provided the first arena in which women began to be involved in politics. In post-colonial times nationalism continues to offer women opportunities for political activity. Yet books on Southeast Asian nationalist movements make very little - if any - mention of women in their ranks. Biographical studies of politically active women in Southeast Asia are also rare. "Women in Southeast Asian Nationalist Movements" is therefore groundbreaking both in highlighting the roles of women in nationalist movements in the region and in taking a biographical approach. In this book, experts on 7 countries examine the experiences of 12 women who have been active in nationalist movements in Southeast Asia. The women selected for study range from well known to little known, and the nationalist movements in which they have been involved date from the early 20th century to the present day. The chapters show women negotiating their own subjectivity and agency at the confluence of colonialism, patriarchal traditions, and modern ideals of national and personal emancipation. We gain a sense of the constraints imposed on them by wider social and political structures, and of what it was like to live in their given time and place.